Tindak Tutur Ilokusi dalam Webinar BKKBN Official - Rizky Devy Wulandari; Mujid Farihul Amin; Riris Tiani (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2022)
BKKBN Official Online Seminar is a platform aimed to give information and educate people, the millenial in particular, about planned family. This study is analyzed speech on BKKBN Official Online Seminar themed " Prevent Stunting for Well Generation and HPV Vaccination before Marriage Protected Together". The source of data is speech that containing Searle's illocution speech act. The objective of this study is to describe types of illocution speech ach found in BKKBN Official Online Seminar. Method uses in this study is scrutinize and taking notes. Results of this study are two types of representative speech act, four types of directive speech act, three types of expressive speech act, one type of comissive speech act and declarative speech act. The result found that representative speech act is dominated because BKKBN online seminar loads speech binding with truth supporting by facts and data.